If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying n + 2(9 + 5n) = 0 n + (9 * 2 + 5n * 2) = 0 n + (18 + 10n) = 0 Reorder the terms: 18 + n + 10n = 0 Combine like terms: n + 10n = 11n 18 + 11n = 0 Solving 18 + 11n = 0 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-18' to each side of the equation. 18 + -18 + 11n = 0 + -18 Combine like terms: 18 + -18 = 0 0 + 11n = 0 + -18 11n = 0 + -18 Combine like terms: 0 + -18 = -18 11n = -18 Divide each side by '11'. n = -1.636363636 Simplifying n = -1.636363636
| 9x-5x+3x+4x=63 | | x*ln(x^2)+ln(2)=0 | | (16/25)^-3/2 | | 16/25^-3/2 | | y^4+9y^2-100=0 | | (16/25)^(-3/2) | | .2x+.1=.7 | | x*ln(x*x)+ln(2)=0 | | -2x=2x+8 | | 11/2x-3/4=1/6 | | N=G-18 | | 2x-1+x+4+36=2x+46 | | 3x+y=45 | | 8(2t-9)=-88 | | 2(f-10)=-34 | | -10(s+2)=-95 | | F(-4)=2x^/x-1 | | -2=-3(2x+4) | | 3(4x-1)=8 | | 3(4s+6)=174 | | ab+c=5solvec | | x^2+22x+115=0 | | 2n+4sobren+1n=2 | | 6(x+7)=-2(5-x) | | -2x=-2x+8 | | 4=4(5x-6) | | 4(2x+7)=9 | | =(2x-5)(3x+8)+7 | | 2n+4sobren+1=2 | | an=n/(n-1),n≥2 | | 14x+2=-2x | | 6/7=42 |